Celostna rehabilitacija bolnikov z možganskimi tumorji - Goljar Kregar, Nika (Rehabilitacija (Ljubljana), 2008)
Improved treatment of patients with brain tumor and increased survival have expanded the role of rehabilitation. The goal of rehabilitation of persons with brain tumor is to prevent complications and to maximize the patients' functional abilities in order to improve their quality of life. Neurorehabilitation principles for persons with brain tumors are mostly similar to those applied to persons with stroke or traumatic brain injury. Since in persons with brain tumors progressive functional decline, fatigue and medical fragility are frequent and the time frames for interventions are usually short, rehabilitation goals must be well-defined. Rehabilitation treatment aims to reduce impairments and to help patients re-learn old skills or develop new ones despite their persisting neurological deficits. Patient and family education, emotional support, psychological counseling, and orthotics may also make an important contribution.
Keywords: možgani; rak (medicina); rehabilitacija; zapleti; zdravljenje